Form Finding of Shell Bridges Using the Pneumatic Forming of Hardened Concrete Construction Principle - Benjamin Kromoser; Thomas Pachner; Chengcheng Tang; Johann Kollegger; Helmut Pottmann (Advances in Civil Engineering)
Concrete shells are fascinating structures. Even thin shells can span over large areas without requiring any columns. If a form-defining load case exists, the shape of the shell can be designed to ensure that the forces in the structure are transferred primarily by the membrane action, which leads to an even distribution of the stresses across the shell surface. Concrete as a material, characterized by high compressive strength and low tensile strength, can be used with a very high degree of utilization. A fundamental problem with building concrete shells is the high effort required for the production of the complicated formwork. A new construction principle called Pneumatic Forming of Hardened Concrete (PFHC) was invented at TU Wien and requires no traditional formwork or falsework during the construction process. An air cushion is used to lift a flat hardened concrete plate, and at the same time, additional post-tensioning cables are tightened to support the transformation of the flat plate into a double-curved shell. One possible application of PFHC is the construction of shell bridges. Here, the shape of the shell has to be designed according to the acting loads and the boundary conditions of the construction method. This paper describes the partly conflicting factors involved in the form-finding process for practical application and the semiautomated workflow for optimizing the geometry of shell bridges. In the first optimization step, the final bridge shape is determined using a particle-spring system or alternatively a thrust-network approach. In the second optimization step, the shell is completed to form a full dome—this is called the reference geometry and is required for the new construction method. Finally, the reference geometry is discretized into single-curved panels by using a mesh-based optimization framework. To frame the presented work, an overview of different experimental and computer-aided form-finding methods is given.